2002
DOI: 10.1001/archotol.128.6.635
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Olfactory Disorders in Relation to Major Causes of Olfactory Loss

Abstract: Among many complaints of olfactory loss, the predominant ones were food related. This loss in QoL seemed to be of greater importance in younger than in older people, and women seem to be affected more strongly than men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
372
2
22

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 458 publications
(438 citation statements)
references
References 20 publications
18
372
2
22
Order By: Relevance
“…Test-retest reliability and validity of the test was confirmed in several studies. [34][35][36] Recently, normative data from 3282 subjects have been published. 37 Each subject wore a sleeping mask to prevent visual identification of odor-dispensing pens.…”
Section: Assessment Of Olfactory Detection Threshold and Olfactory Idmentioning
confidence: 99%
“…Test-retest reliability and validity of the test was confirmed in several studies. [34][35][36] Recently, normative data from 3282 subjects have been published. 37 Each subject wore a sleeping mask to prevent visual identification of odor-dispensing pens.…”
Section: Assessment Of Olfactory Detection Threshold and Olfactory Idmentioning
confidence: 99%
“…32 The most common known etiologies for anosmia are nasal/sinus congestion, upper respiratory tract infection, current smoking, head trauma, stroke, and epilepsy. 23,[33][34][35] Some investigators theorize that olfactory declines may be a consequence of autoimmune mechanisms 36 or neurodegenerative diseases. 37 The prognosis of olfactory dysfunction is influenced by certain demographic and clinical factors.…”
Section: Discussionmentioning
confidence: 99%
“…: in some studies a relation was observed between the degree of olfactory loss and the risk of hazardous events [1,2]. Furthermore, nutritional status and many other topics related to the quality of life may be affected by the impairment of olfactory function [3], and loss of smell is accompanied by an increased risk of depression [4]. In addition, it is present in up to the 90% of Parkinson's Disease patients, and is considered one of the most prevalent troublesome nonmotor problems in this disease [5].…”
Section: Introductionmentioning
confidence: 99%